P374 Non-alcoholic fatty liver disease in inflammatory bowel disease: Prevalence and risk factors. (16th January 2018) - Losurdo, G; Iannone, A; Mangia, M; Shahini, E; Albano, F; Rizzi, S F; La Fortezza, R F; Lovero, R; Contaldo, A; Barone, M; Leandro, G; Ierardi, E; et al.
Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is common in inflammatory bowel diseases (IBD). Herein, NAFLD prevalence and risk factors in a large IBD cohort were evaluated and compared with that of a non-IBD sample. Methods: Crohn's disease/ulcerative colitis outpatients referring to IBD service of our Gastroenterology Unit were enrolled. Subjects affected by functional and motor gastrointestinal disorders, in whom IBD was ruled out, referring to general outpatient service in the same area, were considered as non-IBD group. Exclusion criteria were based on previous diagnosis of non-NAFLD chronic liver diseases and secondary causes of fat liver overload. Characteristics of IBD and liver status were collected. Risk factors for metabolic syndrome were analysed. Ultrasonographic presence and degree of steatosis were assessed. Data were examined by univariate and multivariate analyses. Results: Four-hundred and sixty-five IBD and 189 non-IBD subjects were consecutively enrolled. NAFLD was found in 28.0% and 20.1% in IBD and non-IBD subjects, respectively ( p = 0.04). IBD patients with NAFLD were younger than non-IBD ones. There was no significant difference in steatosis grade and association between NAFLD and IBD behaviour, extension, activity and drugs. In the IBD group, multivariate analysis demonstrated that NAFLD was independently associated to metabolic syndrome (OR = 2.24, 95% CI 1.77–28.81), diabetes (OR = 1.71, 95% CI 1.43–12.25), fasting blood glucose (OR = 1.36, 95% CI 1.13–1.68) and abdominal circumference (OR = 1.68, 95% CI 1.15–14.52). Conclusions: NAFLD is more common and occurs at a younger age in IBD than in non-IBD subjects. However, further investigation is required to ascertain possible NAFLD pathogenic IBD-related factors other than conventional/metabolic ones.